2018
DOI: 10.1161/jaha.118.009360
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Acute Lesions Versus White Matter Hyperintensities on Stroke Recovery

Abstract: BackgroundUnderstanding how the size of acute lesions and white matter hyperintensities (WMH) impact stroke recovery can improve our ability to predict outcomes and tailor treatments. The aim of this exploratory study was to investigate the role of acute lesion volume and WMH volume on longitudinal recovery of specific sensory, motor, and cognitive impairments after stroke using robotic and clinical measures.Methods and ResultsEighty‐two individuals were assessed at 1, 6, 12, and 26 weeks poststroke with robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…They used two distinct methodologies, Node Destruction (NoDe) and Change in Connectivity (ChaCo), respectively, to evaluate the effect of stroke lesion on nodes and edges of the structural connectome. The results showed that the impaired sensation may result from stroke lesions in the anterior parietal and superior temporal lobes, and the extent of the acute infarct was strongly associated with somatosensory deficits, which is in accordance with the conclusion that lesion volume could explain the severity of clinical symptoms (75). Besides that, the results also suggested that disruption of white matter pathways to the identified regions (mainly in the supramarginal and transverse temporal gyri) accounts for a larger proportion of variation in the sensation outcomes, which indicates that white matter integrity is important for normal processing of somatosensory inputs.…”
Section: Structural Brain Connectomesupporting
confidence: 87%
“…They used two distinct methodologies, Node Destruction (NoDe) and Change in Connectivity (ChaCo), respectively, to evaluate the effect of stroke lesion on nodes and edges of the structural connectome. The results showed that the impaired sensation may result from stroke lesions in the anterior parietal and superior temporal lobes, and the extent of the acute infarct was strongly associated with somatosensory deficits, which is in accordance with the conclusion that lesion volume could explain the severity of clinical symptoms (75). Besides that, the results also suggested that disruption of white matter pathways to the identified regions (mainly in the supramarginal and transverse temporal gyri) accounts for a larger proportion of variation in the sensation outcomes, which indicates that white matter integrity is important for normal processing of somatosensory inputs.…”
Section: Structural Brain Connectomesupporting
confidence: 87%
“…There is first evidence for the association of WMH extent and recovery from neglect. Hawe and colleagues (2018) reported a significant relation between chronic neglect performance and the calculated overall volumes of stroke lesion and WMH, whereas the volumes of lesion and of WMH alone were not associated with neglect recovery. Their finding corresponds well with our observation that the combination of stroke lesion and WMH volume-maps is a better predictor than one of those maps alone for neglect severity in acute stroke patients.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, WMH have received more attention, as they are associated with an increased risk of stroke ( Debette and Markus, 2010 ), stroke recurrence ( Andersen et al, 2017 , Georgakis et al, 2019 ), mortality ( Debette and Markus, 2010 , Georgakis et al, 2019 ), disturbed mobility ( Guttmann et al, 2000 ), cognitive decline ( Qi et al, 2019 , Valdés Hernández et al, 2013 ), and dementia ( Debette and Markus, 2010 , Georgakis et al, 2019 ). Moreover, WMH are reported to be specifically related to recovery of cognitive but not other poststroke impairments ( Hawe et al, 2018 , Khan et al, 2019 ). WMH are also linked to cognitive deficits, as studies find associations of WMH extent with worse cognitive functions in Parkinson’s disease ( Huang et al, 2020 , Linortner et al, 2020 , Liu et al, 2021 ), as well as severity and rate of progression of primary progressive aphasia ( Meier et al, 2020 , Odolil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, subjects who had persistent proprioceptive deficits also had greater lesion volume. While lesion volume has been associated with poor recovery ( Löuvbld et al, 1997 ; Saunders et al, 1995 ), a more recent view is that lesion volume is not predictive of recovery without the addition of lesion location ( Chen et al, 2000 ; Feng et al, 2015 ; Zhu et al, 2010 ), nor does it relate specifically to sensory, motor, or cognition ( Hawe et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%